Factors associated with caregiver distress among home care clients in New Zealand: Evidence based on data from interRAI Home Care assessment. (27th November 2021) - Abey‐Nesbit, Rebecca; Van Doren, Shauni; Ahn, SangNam; Iheme, Linda; Peel, Nancye M.; Declercq, Anja; Hirdes, John; Allore, Heather; Jamieson, Hamish A.
Abstract: Objective: To identify factors associated with caregiver distress among home care clients in New Zealand. Methods: The cohort consisted of 105, 978 community‐dwelling people aged 65 years or older requiring home care services in New Zealand who had at least one informal caregiver. Bivariate and multivariable logistic regression analyses were used to identify factors associated with caregiver distress. Results: Variables associated with risk of caregiver distress included Depression Rating Scale score, aggressive behaviour symptoms, primary informal caregiver relationship to patient, Cognitive Performance Scale score, Changes in Health, End‐stage disease, and Signs and Symptoms Scale score, informal care time, secondary informal caregiver relationship to care recipient, activities of daily living hierarchy scale score and any hospitalisation. Conclusions: The study has identified important characteristics that are associated with caregiver stress. These results suggest that caregiver distress can be relieved by promoting protective factors and aiming to reduce risk factors among home care clients in New Zealand.